(3GdLGeY aj GdCOhjI GdeaQOIs - (3YHO Gddg Hf CMeO GdeGdbj, VjGA GdOjf, GHf GdHjWGQ , J (B646 (3g` s
(3ChdgG (B:s
(3jfbUgG SWhQ ef GdebOeI hChdi UaMGJgG ZjQ hGVMI hJbY COhjI GdNjQ GdeScfg dChLGYgG hGdbQhMGJ GdedjfI hEMJeGd fUa s
(3BNQgG (B:s
(3hChOY ajg eY Pdc CeQGVkG JejR HgG Yf ZjQI s
(3fSNI KGdKI UMjMIs
(3jfJbUgG SWhQ ef GdebOeIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B67s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH Gdhd (B- (3U (B60 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs